ω3 Polyunsaturated Fatty Acids as Immunomodulators in Colorectal Cancer: New Potential Role in Adjuvant Therapies - Miccadei, Stefania; Masella, Roberta; Mileo, Anna Maria; Gessani, Sandra (Frontiers in Immunology, 2016)
Diet composition may affect the onset and progression of chronic-degenerative diseases, including cancer, whose pathogenesis relies on inflammatory processes. Growing evidence indicates that diet and its components critically contributes to human health, affecting the immune system, secretion of adipokines and metabolic pathways. Colorectal cancer (CRC) is one of the leading causes of death worldwide. Antineoplastic drugs are widely used for CRC treatment but drug resistance and/or off-target toxicity limit their efficacy. Dietary ω3 polyunsaturated fatty acids (PUFA) has been gaining great interest in recent years as possible anti-inflammatory and anti-cancer agents especially in areas such as the large bowel, where the pro-inflammatory context promotes virtually all steps of colon carcinogenesis. Growing epidemiological, experimental and clinical evidence suggests that ω3 PUFA may play a role in several stages of CRC management exhibiting antineoplastic activity against human CRC cells, improving the efficacy of radiation and chemotherapy, ameliorating cancer-associated secondary complications and preventing CRC recurrence. These effects are most likely related to the immunomodulatory activities of ω3 PUFA that are able to influence several aspects of the inflammatory process ranging from inflammasome activation, leukocyte recruitment, production of immune mediators to differentiation and activation of immune cells. In this review, we will focus on potential use of ω3 PUFA an adjuvant agents together with chemo/radiotherapy, highlighting the immunomodulatory effects most likely responsible for their beneficial effects in different stages of CRC management.